Islamic Corporate Culture and Customer Satisfaction and Their Influence on Islamic Bank Performance: Evidence from Indonesia - Kenedi, Jon; Amar, Syamsul; Rasyid, Rosyeni; Ali, Helmi (Journal of Posthumanism, 2025)
This study aims to identify the influence of Islamic corporate culture on the performance of Islamic banks, both directly and through customer satisfaction. This study also aims to determine the effect of customer satisfaction on the performance of Islamic banks. The research design used was a survey with a quantitative approach. Using a questionnaire as the research instrument, data were collected from 220 respondents from 44 Islamic banks operating in 14 regencies and cities in West Sumatra Province, Indonesia. The study findings indicate that Islamic corporate culture has a positive impact on the performance of Islamic banks, while customer satisfaction has no significant effect on the performance of Islamic banks. Furthermore, it was found that customer satisfaction does not mediate the relationship between Islamic corporate culture and Islamic bank performance. This paper can be useful for Islamic bank managers in creating an Islamic corporate culture that drives Islamic bank performance. This paper is unique in that it finds that customer satisfaction has no impact on the performance of Islamic companies/banks in areas where the community is very devout in practicing Islamic teachings. This study aims to identify the influence of Islamic corporate culture on the performance of Islamic banks, both directly and through customer satisfaction. This study also aims to determine the effect of customer satisfaction on the performance of Islamic banks. The research design used was a survey with a quantitative approach. Using a questionnaire as the research instrument, data were collected from 220 respondents from 44 Islamic banks operating in 14 regencies and cities in West Sumatra Province, Indonesia. The study findings indicate that Islamic corporate culture has a positive impact on the performance of Islamic banks, while customer satisfaction has no significant effect on the performance of Islamic banks. Furthermore, it was found that customer satisfaction does not mediate the relationship between Islamic corporate culture and Islamic bank performance. This paper can be useful for Islamic bank managers in creating an Islamic corporate culture that drives Islamic bank performance. This paper is unique in that it finds that customer satisfaction has no impact on the performance of Islamic companies/banks in areas where the community is very devout in practicing Islamic teachings.